Chromogranin A: As A Tumor Marker for Neuroendocrine Tumors Diagnosis, Follow-up & Its Correlation with Response to Somatostatin Analogues - Mohammed AL-Naqqash, Manwar A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Chromogranin A is a useful tumor marker for neuroendocrine tumors (NETs) diagnosis & follow-up, Octreotide (somatostatin-long acting repeatable (SAS-LAR)) is an established treatment for NETs. Studies regarding the relation between response to SAS-LAR & the change in Chromogranin A (CgA) plasma level are still lacking.Objectives: To determine the association between the using of Octreotide (SAS-LAR) and CgA level on time sequence & clinical status.Patients & methods: a prospective observational study included 38 neuroendocrine patients in The Oncology Teaching Hospital/medical city complex/Baghdad, started at September 2013 till May 2016; assessing their circulating chromogranin A (CgA) plasma levels on multiple occasions(0,2 and 4 months) by ELISA technique and its correlation with response to somatostatin analogues (SAS-LAR) in those patients.Results: the study recruited 38 neuroendocrine patients. 21 (55%) of them were males, 23 (60%) patients were older than 50 years old & 17 (44%) had metastasis to different sites. Somatostatin analogues (octreotide 30mg) was administered to 20 out of 38 (52.6%) studied patients. Serial CgA tests were performed in (17 out of 20) patients used SAS-LAR, with a change in mean value from (225.3 U/L) pre-using the agent to (17.5 U/L) two months after its use & to (8.7 U/L) four months after its use (p=0.009, p=0.002 respectively) while the change in mean of CgA level was from (205.9 U/L) to (200.9 U/L) in 10 patients who did not use Octreotide (p=0.2).Also results showed that no statistically significant difference in mean value of CgA pre & two months after using Octreotide with regard to grade of the tumor.Conclusions: Plasma CgA is a reliable marker for NETs (regarding diagnosis, prognosis and response to treatment including somatostatin analogues).All patients with NETs should undergo a baseline plasma CgA level at diagnosis. Serial assessment of circulating CgA could be done for NET patients when there is baseline elevation of CgA level in circulation